Nutrition Knowledge is Correlated with a Better Dietary Intake in Adolescent Soccer Players: A Cross-Sectional Study - Danilo C. Noronha; Monique I. A. F. Santos; Adrianny A. Santos; Lizia G. A. Corrente; Rúbia K. N. Fernandes; Anna C. A. Barreto; Ronyclay G. J. Santos; Rafaela S. Santos; Luís P. S. Gomes; Marcus V. S. Nascimento (Journal of Nutrition and Metabolism)
Nutrition education is one of the factors that may help to promote behavior change and therefore may improve the dietary habits of adolescent soccer players. However, information about the relationship between nutrition knowledge (NK) and the dietary behavior of these athletes is scarce. The purpose of this study was to evaluate the eating habits of adolescent soccer players and analyse the correlations among dietary intake and NK. Seventy-three Brazilian adolescent soccer players (aged 14–19 years), from four professional clubs, underwent anthropometric evaluation and completed 3-day food records. Misreporting of energy intake was evaluated and the dietary intake data were energy-adjusted and compared with recommendations for athletes and dietary reference intakes. The athletes also answered a questionnaire about barriers for healthy eating and a nutrition knowledge test divided into three sections: Basic Nutrition Knowledge (BNK), Sports Nutrition Knowledge (SNK), and Food Pyramid Nutrition Knowledge (FPNK). The participants showed a low NK (54.6%) and an inadequate intake of fruits, vegetables, dairy, carbohydrates, and micronutrients. A positive correlation was found between the ingestion of phosphorus and FPNK as well as among calcium and both SNK and Total NK (p<0.05). Sodium intake was negatively correlated with all categories of the NK test (p<0.05). The adolescents reported that the principal barriers for adopting a healthy diet were the lack of willpower and a busy lifestyle. In this context, nutrition education is recommended and should also provide practicable healthy eating goals according to athletes´ lifestyle as well as target motivational barriers to increase adherence.